The function `y = log(tan(pi/4 + x/2))` .

`dy/dx = (1/(tan(pi/4 + x/2)))*sec^2(pi/4 + x/2)*(1/2)`

= `((cos(pi/4 + x/2))/(sin(pi/4 + x/2)))*sec^2(pi/4 + x/2)*(1/2)`

= `(1/(sin(pi/4 + x/2)))*sec (pi/4 + x/2)*(1/2)`

= `1/(sin(pi/4 + x/2)*cos(pi/4 + x/2)*2)`

= `1/(sin(2*(pi/4 + x/2)))`

= `1/(sin(pi/2+x))`

= `1/(cos x)`

= sec x

`dy/dx -...

## Unlock

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

The function `y = log(tan(pi/4 + x/2))` .

`dy/dx = (1/(tan(pi/4 + x/2)))*sec^2(pi/4 + x/2)*(1/2)`

= `((cos(pi/4 + x/2))/(sin(pi/4 + x/2)))*sec^2(pi/4 + x/2)*(1/2)`

= `(1/(sin(pi/4 + x/2)))*sec (pi/4 + x/2)*(1/2)`

= `1/(sin(pi/4 + x/2)*cos(pi/4 + x/2)*2)`

= `1/(sin(2*(pi/4 + x/2)))`

= `1/(sin(pi/2+x))`

= `1/(cos x)`

= sec x

`dy/dx - sec x = 0`

**If `y = log(tan(pi/4 + x/2))` , `dy/dx - sec x = 0` **